The impact of immigration and vaccination in reducing the incidence of hepatitis B in Catalonia (Spain) - Oviedo Manuel; Muñoz M; Carmona Gloria; Borrás Eva; Batalla Joan; Soldevila Nuria; Domínguez Angela (BMC, 2012)
Abstract Background The Hepatitis B virus (HBV) infection is a major cause of liver disease and liver cancer worldwide according to the World Health Organization. Following acute HBV infection, 1-5% of infected healthy adults and up to 90% of infected infants become chronic carriers and have an increased risk of cirrhosis and primary hepatocellular carcinoma. The aim of this study was to investigate the relationship between the reduction in acute hepatitis B incidence and the universal vaccination programme in preadolescents in Catalonia (Spain), taking population changes into account, and to construct a model to forecast the future incidence of cases that permits the best preventive strategy to be adopted. Methods Reported acute hepatitis B incidence in Catalonia according to age, gender, vaccination coverage, percentage of immigrants and the year of report of cases was analysed. A statistical analysis was made using three models: generalized linear models (GLM) with Poisson or negative binomial distribution and a generalized additive model (GAM). Results The higher the vaccination coverage, the lower the reported incidence of hepatitis B (p <0.01). In groups with vaccination coverage > 70%, the reduction in incidence was 2-fold higher than in groups with a coverage <70% (p <0.01). The increase in incidence was significantly-higher in groups with a high percentage of immigrants and more than 15% (p <0.01) in immigrant males of working age (19-49 years). Conclusions The results of the adjusted models in this study confirm that the global incidence of hepatitis B has declined in Catalonia after the introduction of the universal preadolescent vaccination programme, but the incidence increased in male immigrants of working age. Given the potential severity of hepatitis B for the health of individuals and for the community, universal vaccination programmes should continue and programmes in risk groups, especially immigrants, should be strengthened.